“Nós somos machistas”: entrevistas com escritores/as brasileiros/as - Christian Grünnagel; Doris Wieser (Estudos de Literatura Brasileira Contemporânea)
This dossier brings together seven interviews carried outat the Frankfurt BookFair in 2013 with the following Brazilian writers: Ana Paula Maia, BeatrizBracher, Bernardo Ajzenberg, Carola Saavedra, Ferréz, Luiz Ruffato andMarcelino Freire. The first part of each interview focusses on gender issues, inparticular on diverging concepts of masculinity and femininity in Braziliansociety and literature. These concepts are based on the theory developed by theAustralian sociologist R. W. Connell, who is one of the most distinguishedcontemporary scholars of masculinities and gender relations. The second partshifts its focus to question about the particularities of each writer‟s work, theirmain aesthetic concerns and the connections between their works.